A Mathematical Model of Communication with Reputational Concerns - Ce Huang; Yuanyuan Zhang; Chong Lai (Discrete Dynamics in Nature and Society)
We investigate a mathematical model where an expert advises a decision maker for two periods. The decision maker is initially unsure about whether the expert is biased or not. After consulting the expert on the decision problem of period one, the decision maker updates belief about the expert’s bias and consults the expert on the problem of period two. We find that more information is delivered in the model’s first period than in the one-period situation of communication.